Kajian Historis Materi Dinasti Umayyah Timur Dalam Pembelajaran Sejarah Kebudayaan Islam Di Sekolah/Madrasah - Lubis, Elfa Fadhilah; Zen, Nurzena (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the historical study of the Umayyad Dynasty material in the learning of Islamic Cultural History (Sejarah Kebudayaan Islam) in schools and Islamic madrasahs. The research uses a qualitative approach with a library research method. Data were collected through documentation techniques by reviewing relevant books, scientific journals, and educational documents related to the Umayyad Dynasty and its implementation in Islamic history learning. The sampling technique used was purposive sampling, selecting sources that are relevant and credible to the research focus. Data analysis was conducted using content analysis, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source triangulation by comparing various literature to obtain reliable and consistent findings. The results of the study show that the Umayyad Dynasty played a significant role in the development of Islamic civilization, particularly in administrative reform, political system development, military expansion, and cultural advancement. In the context of Islamic Cultural History learning, the material of the Umayyad Dynasty is highly relevant in shaping students’ historical understanding and character values such as leadership, discipline, and responsibility. However, learning practices are still mostly conventional and focus on memorization. Therefore, innovative and contextual learning approaches are needed to improve students’ engagement and critical thinking skills. In conclusion, the historical study of the Umayyad Dynasty material is essential for strengthening both cognitive understanding and character education in Islamic education.